2015
DOI: 10.1002/esp.3783
|View full text |Cite
|
Sign up to set email alerts
|

Englacial and subglacial water flow at Skálafellsjökull, Iceland derived from ground penetrating radar,in situGlacsweb probe and borehole water level measurements

Abstract: We reconstruct englacial and subglacial drainage at Skálafellsjökull, Iceland, using ground penetrating radar (GPR) common offset surveys, borehole studies and Glacsweb probe data. We find that englacial water is not stored within the glacier (water content~0-0.3%). Instead, the glacier is mostly impermeable and meltwater is able to pass quickly through the main body of the glacier via crevasses and moulins. Once at the glacier bed, water is stored within a thin (1 m) layer of debris-rich basal ice (2% water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 97 publications
2
44
0
Order By: Relevance
“…Observations by Hart et al (2015) using wireless pressure sensors installed across the basal till layer in a glacier in Norway showed that, while a sensor at the ice-till interface shows clear diurnal variations, another one placed a short distance away inside the till layer can show a signal very similar to our disconnected boreholes. This could be a problem affecting some of our sensors, as borehole drilling could eventually penetrate the till.…”
Section: Data Interpretation Caveatsmentioning
confidence: 99%
“…Observations by Hart et al (2015) using wireless pressure sensors installed across the basal till layer in a glacier in Norway showed that, while a sensor at the ice-till interface shows clear diurnal variations, another one placed a short distance away inside the till layer can show a signal very similar to our disconnected boreholes. This could be a problem affecting some of our sensors, as borehole drilling could eventually penetrate the till.…”
Section: Data Interpretation Caveatsmentioning
confidence: 99%
“…The results from the 2008 and 2011 surveys were reported in Hart et al (2015), and the same techniques are used to analyse the 2012 data. The results from the 2008 and 2011 surveys were reported in Hart et al (2015), and the same techniques are used to analyse the 2012 data.…”
Section: Gpr Resultsmentioning
confidence: 99%
“…We calculate a mean attenuation value (see Hart et al, 2015, for details), and apply this as the best-fit line to the data, as returned power verses depth. These values were plotted as a histogram and three peaks are identified and these were used to quantify bed strength (see figure 6 in Hart et al, 2015). These values were plotted as a histogram and three peaks are identified and these were used to quantify bed strength (see figure 6 in Hart et al, 2015).…”
Section: Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations by Hart et al (2015) using wireless pressure sensors installed across the basal till layer in a glacier in Norway showed that, while a sensor in the ice-till interface shows clear diurnal variations, another one placed a short distance away…”
mentioning
confidence: 99%